2016
DOI: 10.17712/nsj.2016.3.20150597
|View full text |Cite
|
Sign up to set email alerts
|

The availability of services for children with autism spectrum disorder in a Saudi population

Abstract: Objective:To assess the perceived availability of various services provided by Autism centers in our region.Methods:A cross sectional study was conducted from March to May 2015 involving health care workers at various governmental and private autism centers in Jeddah, Kingdom of Saudi Arabia. A structured 30-item questionnaire was designed to assess their demographics, training, experience, and the availability of various services at their centers.Results:Twelve autism centers were included and 136 employees p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 12 publications
0
10
0
2
Order By: Relevance
“…In Ahmadi's study, parents' unawareness of accessing the required services was documented [26]. Studies signified accessibility problems, such as limitedservice providers, long waiting times, and the lack of transportation [27][28][29] deficiencies in service access, including referral problems for essential services in Jeddah, Saudi Arabia [30].…”
Section: Discussionmentioning
confidence: 99%
“…In Ahmadi's study, parents' unawareness of accessing the required services was documented [26]. Studies signified accessibility problems, such as limitedservice providers, long waiting times, and the lack of transportation [27][28][29] deficiencies in service access, including referral problems for essential services in Jeddah, Saudi Arabia [30].…”
Section: Discussionmentioning
confidence: 99%
“…2 Early recognition is needed for early implementation of multidisciplinary treatment, which in turn improves the outcome. 3 , 4 Enhanced public awareness is needed to prevent delays in the provision of such services. 5 Improved awareness would also help in minimizing possible associated social stigma.…”
mentioning
confidence: 99%
“…The findings of Płatos and Pisula in 2019 showed that despite the growing number of adolescents and young adults with ASD, there is little information about the necessary services and the existing barriers. In their study, the barriers that parents stated included difficulty in accessing services, not being eligible to receive services, difficult access to information about services, and expensive costs of services [24]. Another study reported that people with ASD had problems with the use of services, lack of regular service delivery, insufficient insurance coverage, and lack of parental involvement in childcare.…”
Section: Resultsmentioning
confidence: 99%